Developing Thematic-Based Physical Activity Models to Enhance Physical Literacy in Early Childhood - Suherman, Asep; Suherman, Adang; Juliantine, Tite; Mahendra, Agus (Mimbar Sekolah Dasar, 2025)
This study aims to develop a thematic-based physical activity model to improve physical literacy in early childhood and to test its effectiveness. The method used is research and development (RD) following the ADDIE procedure, which includes analysis, design, development, implementation, and evaluation stages. The research sample consisted of 41 children aged 4-5 years. Instruments used were a needs analysis questionnaire, validation questionnaires from experts on the physical activity model and physical literacy, a learning module validation questionnaire, and a physical literacy observation sheet. The findings show that the developed model is very good. The effectiveness test using a pre-experimental design showed a significant improvement in children's physical literacy, with an average pretest score of 68.2 and posttest score of 89, and an N-gain score of 0.52 (moderate category). Interview results indicated a positive impact of the model on children's holistic development, including increased confidence, cooperation, and motivation for physical activity, despite challenges such as limited facilities, classroom management, and children's egocentric attitudes. In conclusion, the thematic-based physical activity model is feasible for use in learning and effective in improving physical literacy in early childhood. According to these findings, early childhood educators can improve children's physical, psychological, social, and cognitive development by incorporating thematic physical activities. They can also promote its inclusion in national literacy policies.